2016
DOI: 10.1002/2015ja021883
|View full text |Cite
|
Sign up to set email alerts
|

The inner magnetosphere ion composition and local time distribution over a solar cycle

Abstract: Using the Cluster/Composition and Distribution Function (CODIF) analyzer data set from 2001 to 2013, a full solar cycle, we determine the ion distributions for H+, He+, and O+ in the inner magnetosphere (L < 12) over the energy range 40 eV to 40 keV as a function magnetic local time, solar EUV (F10.7), and geomagnetic activity (Kp). Concentrating on L = 6–7 for comparison with previous studies at geosynchronous orbit, we determine both the average flux at 90° pitch angle and the pitch angle anisotropy as a fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
88
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(97 citation statements)
references
References 53 publications
9
88
0
Order By: Relevance
“…Drifting plasma sheet ions are energized by the increased magnetic field strength (as well as temporarily energized by field fluctuations). Aging of the drifting plasma over a~24 h period led to an enhanced heavy ion content [Smith and Bewtra, 1978;Fok et al, 1991;Ebihara et al, 1998;Ferradas et al, 2015;Kistler and Mouikis, 2016]. This plasma mimics the presence of local in situ acceleration of the low-energy population.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Drifting plasma sheet ions are energized by the increased magnetic field strength (as well as temporarily energized by field fluctuations). Aging of the drifting plasma over a~24 h period led to an enhanced heavy ion content [Smith and Bewtra, 1978;Fok et al, 1991;Ebihara et al, 1998;Ferradas et al, 2015;Kistler and Mouikis, 2016]. This plasma mimics the presence of local in situ acceleration of the low-energy population.…”
Section: Discussionmentioning
confidence: 89%
“…Since O + is a major constituent of the ionosphere, and not of the solar wind, the presence of high-density O + (along with He + ) is strongly indicative of an ionospheric source. These losses result in changes in the composition that are energy (i.e., drift) dependent [Ferradas et al, 2015;Kistler and Mouikis, 2016]. (a) Direct and local acceleration of ionosphere and/or plasmasphere ions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yau et al (1988) parameterised the ionospheric ion outflow and found that the O + outflow rate increased exponentially with Kp as exp(0.5 Kp). Other studies that have shown a clear correlation between O + and geomagnetic activity are Peterson et al (2001), Cully et al (2003), and Kistler and Mouikis (2016). The O + density close to the mid-latitude magnetopause was shown by Bouhram et al (2005) to also increase exponentially with Kp.…”
Section: Introductionmentioning
confidence: 94%
“…Spacecraft observation shows that the density of oxygen in the plasma sheet can be the dominating ion species during storm-time conditions (André & Cully, 2012;Kistler & Mouikis, 2016;Kistler et al, 2005Kistler et al, , 2006Mouikis et al, 2010). During such conditions, ionospheric outflow from high latitudes enriches the magnetospheric lobes with cold oxygen.…”
Section: Simulation Setupmentioning
confidence: 99%